Hash-based Byzantine fault tolerant agreement with enhanced view consistency. (1st January 2014) - Saini, Poonam; Singh, Awadhesh Kumar
This paper presents an authentication-based Byzantine fault tolerant agreement protocol that is capable of detecting the tentative failures in transaction processing systems. The protocol employs a cryptographic hash function to detect crash as well as a few more types of commonly faced arbitrary behaviours manifested by the participating server replicas in the system. We show that the use of hash functions can successfully handle various types of (arbitrary) faults. In addition, it suggests a preemptive mechanism to proactively detect the malicious replicas. The protocol avoids frequent view changes that contributes to the liveness of the system and ensures continuity in transaction processing.